Implementation of Ksatria Story Book in Embedding Leadership Character Values in Children 5-6 Years Old - Fitri, Sinthia Nurul; Waluyo, Edi (BELIA: Early Childhood Education Papers, 2020)
One of the character problems in early childhood is the lack of ability to be responsible, communicate, and cooperate. These three main behaviors are characteristics of leadership behavior. Responding to this, the researcher uses the Ksatria storybook media in this study to help kindergarten students understand and develop leadership behaviors. This research uses quantitative research method with Pre-Experimental Design in the form of One-Group Pretest-Posttest Design. The data is taken using a questionnaire filled by class teachers. The sampling technique in this study is a purposive sampling technique. The sample is 30 students in the B3 class of TK IT (Islamic kindergarten) Al Hidayah Karanggede, Boyolali, as well as an experimental class that received the Knight Storybook application. The data is collected using a leadership character value scale. While the data analysis using hypothesis testing paired sample t-test. This study shows that there are differences in leadership character behavior of children aged 5-6 years before and after getting treatment and there is the influence of the Ksatria storybook in instilling leadership behavior in children aged 5-6 years. It is proven based on statistical calculations, that is obtained the value of sig (2-tailed) 0,000 <0.05 which means that Ho is rejected and Ha is accepted so that the hypothesis test is accepted with the direction of a positive relationship. Thus, there are differences in leadership character behavior in early childhood after getting the Ksatria storybook method. In other words, the Ksatria book can be an alternative to planting leadership attitudes and behaviors in Kindergarten.